Николай Александрович Добролюбов: биография отдельного лица / В. С. Никоненко - Никоненко Виталий Сергеевич (Мыслители прошлого, 1985)
Экземпляры: аб (20180123) / Инвентарный номер: 016783 / Цена: 0.25 / Авт.знак: Н 64 / ГРНТИ: 02.91.09 / ББК: 87.3(2)